Replication in labor economics - W. Robert Reed (IZA World of Labor, 2017)
There is growing concern that much of the empirical research in labor economics and other applied areas may not be reproducible. Correspondingly, recent years have seen an increase in replication studies published in economics journals. Despite this increase, there are many unresolved issues about how replications should be done, and how to interpret their results. Replications have demonstrated a potential for clarifying the reliability and robustness of previous research. Much can be done to encourage more replication research, and to exploit the scientific value of existing replication studies.
Keywords: C13; C18; B4; J01; 330; reproducibility; replication; replication crisis; labor economics